2008
DOI: 10.1186/1471-2415-8-21
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to glaucoma screening and education in Nepal

Abstract: Background: Glaucoma is a major cause of blindness worldwide and an increasingly significant global health problem. Glaucoma prevention and management efforts have been challenging due to inherent difficulty in developing a simple and cost-effective screening plan, limited access to health care and educational resources, poverty, and inadequate knowledge of the disease, particularly in developing countries. Starting in 2004 the Tilganga Eye Centre in Kathmandu, Nepal has provided targeted glaucoma screening, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In the present study, 92.3% of those diagnosed with glaucoma‐related conditions were previously unaware of their condition, which is consistent with results from population‐based glaucoma screening in China (82%‐95.9%) . This proportion is similar to that reported in other low and middle‐income countries, including Nepal (96%) and India (92.6%), and is significantly higher than that reported in richer countries, such as Ireland (49%), Australia (51%) and the Netherlands (52.9%) . The high prevalence of undiagnosed glaucoma is likely due to a combination of poor access to healthcare and the absence of subjective symptoms until late stages of disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, 92.3% of those diagnosed with glaucoma‐related conditions were previously unaware of their condition, which is consistent with results from population‐based glaucoma screening in China (82%‐95.9%) . This proportion is similar to that reported in other low and middle‐income countries, including Nepal (96%) and India (92.6%), and is significantly higher than that reported in richer countries, such as Ireland (49%), Australia (51%) and the Netherlands (52.9%) . The high prevalence of undiagnosed glaucoma is likely due to a combination of poor access to healthcare and the absence of subjective symptoms until late stages of disease.…”
Section: Discussionsupporting
confidence: 89%
“…3,7 This proportion is similar to that reported in other low and middle-income countries, including Nepal (96%) and India (92.6%), and is significantly higher than that reported in richer countries, such as Ireland (49%), Australia (51%) and the Netherlands (52.9%). 6,[31][32][33][34][35] The high prevalence of undiagnosed glaucoma is likely due to a combination of poor access to healthcare and the absence of subjective symptoms until late stages of disease. In the present study, only four of 277 (1.44%) glaucoma suspects had an IOP ≥ 30 mmHg at initial screening, that is, in a range which might be symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found the majority of pa ents having POAG which is similar to other studies conducted in Nepal and [8][9][10][11][12][13] other south Asian countries. The study by Dr. Sah R. P. et al was a community based cross sec onal study done in 1600 10 pa ents above 40 years in Sunsari district of Nepal .…”
Section: Discussionsupporting
confidence: 89%
“…A novel approach to screening and patient education has been adopted by TIO to promote awareness, screening and follow up of patients [37]. …”
Section: Discussionmentioning
confidence: 99%